2008
DOI: 10.1017/s1751731108002243
|View full text |Cite
|
Sign up to set email alerts
|

Colour differences among carcasses graded with similar score for conformation and fatness

Abstract: In a population of 268 yearling bulls, those carcasses graded as U 2 , U 0 or U 1 for beef carcass conformation (n 5 240) and those graded as 2 2 , 2 0 or 2 1 for beef carcass fatness (n 5 213) were selected to study the efficiency of carcass weight, carcass dimensions and instrumental colour of latissimus dorsi, rectus abdominis and subcutaneous fat, to discriminate among these carcass grades, in a population of high-muscled and very lean carcasses from young bulls. The increase in conformation grade meant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Carcass compactness has been reported to have correlated with subjective conformation score, perimeter of the leg and width of the leg, and strongly correlated with cold carcass weight (Diaz et al, 2004;Albertí et al, 2005;Indurain et al, 2008). The appearance of 'blockiness' of the whole carcass has been shown to have a positive influence on conformation score (Indurain et al, 2008).…”
Section: --mentioning
confidence: 99%
See 1 more Smart Citation
“…Carcass compactness has been reported to have correlated with subjective conformation score, perimeter of the leg and width of the leg, and strongly correlated with cold carcass weight (Diaz et al, 2004;Albertí et al, 2005;Indurain et al, 2008). The appearance of 'blockiness' of the whole carcass has been shown to have a positive influence on conformation score (Indurain et al, 2008).…”
Section: --mentioning
confidence: 99%
“…The appearance of 'blockiness' of the whole carcass has been shown to have a positive influence on conformation score (Indurain et al, 2008). The use of this index as a measure of carcass value could be possible with the introduction of VIA systems in UK lamb abattoirs.…”
Section: --mentioning
confidence: 99%
“…Ils sont également en accord avec l'étude de Keane et Allen (1999) qui indique que des boeufs de 720 kg de poids vif conduisent à des viandes plus jaunes (avec un indice b* supérieur) que celles des boeufs moins lourds (640 kg). En revanche, il semble que l'augmentation conjointe du poids de carcasse et de la conformation (307 à 340 kg ; U-à U+) entraîne une diminution des indices de jaune et de rouge du muscle latissumus dorsi (Indurain et al 2008), les conformations supérieures étant en général associées à une proportion supérieure de fibres blanches, moins pigmentées que les fibres rouges (Jurie et al 1995).…”
Section: / Une Viande Plus Rouge Et Plus Sombre Lorsque Les Carcassesunclassified
“…The reflectance spectrum obtained by spectrophotometry, as well as the trichromatric coordinates of CIE L*a*b*, are fast, non-destructive, online and readily available methods to determine meat colour (Ripoll et al 2008). Instrumental methods based in spectra of colour are able to appreciate individual L*, a*, b* coordinates, as reported by Denoyelle & Berny (1999) and Indurain et al (2008) in surface of veal carcases in the abattoir. Furthermore, studies on meat colour have reported a positive correlation between the a* index and the visual evaluation of colour by consumers (Chan et al 1995).…”
Section: Introductionmentioning
confidence: 99%